Civil servants' commitment to change: a factor of success regarding the reform of public budgeting and accounting in the State of Brandenburg? - Johannes Niklas Holtz (Universitätsverlag Potsdam, 2018)
This study investigates the reform of the public budgeting and accounting system (Doppik) in Brandenburg. On the one hand, this thesis aims to identify the key variables shaping employees' commitment to change and, on the other hand, to examine the extent employees' commitment to change influences the implementation process of the reform. The results of this study show that the commitment of civil servants towards the Doppik is primarily determined by the content, but also by the context of the reform. Moreover, it is revealed for the case of Brandenburg that civil servants' affective commitment to change has a significant positive influence on the perceived success of the reform implementation. The results of the study are not only of high scientific importance, but also of practical relevance. The recommendations developed in this study offer grounded guidelines on how to successfully implement the Doppik on local level in Brandenburg. – – Diese Studie untersucht die Reform des öffentlichen Haushalts- und Rechnungswesens (Doppik) in Brandenburg. Zum einen ist das Ziel, die Schlüsselvariablen zu identifizieren, welche die Reformbereitschaft der Mitarbeiter determinieren. Zum anderen soll untersucht werden, inwieweit die Reformbereitschaft der Mitarbeiter den Umsetzungsprozess der Reform beeinflusst. Die Ergebnisse dieser Studie zeigen, dass Reformbereitschaft der Mitarbeiter gegenüber der Doppik vor allem durch den Inhalt der Reform, aber auch durch den Kontext der Reform bestimmt wird. Schließlich zeigt sich für den Fall Brandenburg, dass die Reformbereitschaft der öffentlich Bediensteten einen signifikanten positiven Einfluss auf den wahrgenommenen Erfolg der Reform besitzt. Die Ergebnisse der Studie sind nicht nur von hoher wissenschaftlicher Bedeutung, sondern auch von praktischer Relevanz. Denn die in dieser Studie herausgearbeiteten Handlungsempfehlungen bieten fundierte Ansatzpunkte darüber, welche Schritte notwendig sind, um die Doppik auf lokaler Ebene in Brandenburg langfristig erfolgreich umzusetzen.
urn:nbn:de:kobv:517-opus4-420792
Keywords: 650; Doppik; accrual accounting; public sector reforms; public change management; change commitment